Early Detection of Mental Health in Hypertensive Elderly: Analyzing Depression, Anxiety, and Stress Levels - Khadijah, Siti; Caturini Sulistiyowati, Endang; Ariani Sulistyowati, Dwi (Interest : Jurnal Ilmu Kesehatan, 2025)
Background: Elderly with hypertension are highly susceptible to psychological disorders, such as depression and anxiety, due to complex physiological and psychosocial changes. However, comprehensive studies examining the interplay of stress, anxiety, and depression within this population remain limited. The purpose of this study is to analyze mental health problems: Depression, Anxiety, Stress in the elderly with hypertension in the Mojosongo Region of Surakarta. Methods: This research method utilised a descriptive analytical survey design with a cross-sectional approach. The sampling technique used purposive sampling with a sample size of 39 elderly people who met the inclusion criteria, namely (1) elderly and (2) having systolic blood pressure ≥140 mmHg. The research instrument used the Depression Anxiety Stress Scale (DASS-21), and data analysis was performed using Pearson's correlation test. Results: Mild depression was dominated by mild hypertension (63.6%), and moderate (76.9%) p=0.571. Mild anxiety was dominated by mild hypertension (54.5%), moderate (76.9%), and severe (75%) p=0.899, mild stress was dominant in mild hypertension (68.2%), moderate (69.2%), and severe (50%) p=0.719. Conclusion: This study found no significant association between the levels of depression, anxiety, or stress and the severity of hypertension. However, given the high prevalence of psychological distress observed in the descriptive findings, healthcare professionals should prioritize mental health screening in elderly patients. Managing these psychological conditions remains crucial for improving overall quality of life, even if it does not directly correlate with blood pressure reduction.